A content analysis of gender representation in Malaysian children's literature / Ramesh Nair - Nair, Ramesh (Research Management Institute (RMI), 2008)
Children's literature serves as a powerful medium through which children construct messages about their roles In society and gender Identity is often central to this construction. Although possessing mental schemas about gender differences is helpful when children organize their ideas of the world around them, problems occur when children are exposed to a constant barrage of uncompromising, gender-schematic sources that lead to stereotyping which in turn represses the full development of the child. This paper focuses on how gender is represented in a selection of Malaysian children's books published in the English language. Relying on the type of content analysis employed by previous feminist social science researchers, I explore this selection of Malaysian children's books for young children and highlight some areas of concern with regard to the construction of maleness and femaleness in these texts. The results reveal Imbalances at various levels Including the distribution of main, supporting and minor characters along gendered lines and the positioning of male and female characters In the visual Illustrations. The stereotyping of these characters In terms of their behavioural traits will be discussed with the aim of drawing attention to the need for us to take concerted measures to provide our children with books that will help them realize their potential to the fullest.